Digital Transformation in Qur’anic and Hadith Pedagogy: Implications for Millennial Engagement - Alinurdin, M.; Nursyamsi, Nursyamsi; Reza, Ali (Journal of Islamic Education Students (JIES), 2025)
Digital transformation in education has become essential in the millennial era, including in Qur’an and Hadith learning at the Madrasah Tsanawiyah level. This study analyzes the relevance of digital innovation in Qur’an and Hadith instruction to the characteristics of millennial learners at MTsN Palopo City. A mixed-methods design was employed, combining descriptive qualitative data from interviews and observations with simple quantitative data from questionnaires administered to 60 students. Data were analyzed using qualitative triangulation and percentage-based quantitative analysis. The results indicate that 78% of students feel more motivated to learn Qur’an and Hadith through digital media, and 82% find mobile applications and e-learning platforms easier to use for understanding the material. Qualitative findings reinforce this, showing that students perceive digital-based learning as more engaging, interactive, and aligned with their technology-oriented habits. Teachers also report increased student engagement, despite challenges related to limited facilities and pedagogical readiness. Overall, the study confirms that digital transformation is highly relevant to Qur’an and Hadith learning for millennial students and underscores the need for creative, collaborative, and technology-based instructional strategies at MTsN Palopo City.